The Beautiful Game: Fair Value, Accountability and Accounting for Player Registrations. Issue 3 (1st March 2022) - Maroun, Warren; van Zijl, Wayne; Chesaina, Rottok; Garnett, Robert
Abstract: Currently, professional football clubs only recognise purchased player contracts (player registrations) in their financial statements. The costs associated with home‐grown players are expensed. Furthermore, acquired player registrations must be held under the historical cost model because revaluations are only permitted when an active market for identical intangible assets is available. This is rare and results in a club's most important asset class either being excluded from the balance sheet or carried at outdated amounts. Comparability among clubs is also compromised. Clubs with a player development strategy are disadvantaged in comparison to those that actively purchase established players because they report weaker balance sheets. Additionally, because the development and changes in the value of registrations are not accounted for over time, current revenues are mismatched with expenses related to investments in assets distorting performance assessments. In response, the current paper develops a normative framework for accounting for player registrations designed to provide a more detailed and transparent account of how clubs manage these important assets. The model complements financial statements by incorporating elements of historical cost and fair value whilst maintaining compliance with IFRS. The model's practical application is illustrated using three well‐known football clubs namely, Arsenal, Everton and Manchester United.